4.1. Slow Archaeology: Technology, Efficiency, and Archaeological Work - (:unkn) unknown (My University, 2016)
Slow archaeology situates contemporary, digital archaeological practice both in the historical tradition of the modern discipline of archaeology and within a discourse informed by calls for Taylorist efficiency. Rather than rejecting the use of digital tools, slow archaeology calls for archaeology to embrace a spirit of critical engagement with the rapidly changing technological landscape in the field. This contribution draws upon lessons from the popular "slow moment" and academic discussions of modernity and speed to consider the impact that the rapid adoption of digital tools has on archaeological practice and knowledge production. Slow archaeology pays particular attention to how digital tools fragment the process of archaeological documentation, potentially deskill fieldwork by relying on digital (Latourian) “blackbox” methods, and erode the sense of place so crucial to archaeological claims of provenience. The result of this critical attention to digital practices is neither a condemnation of new tools nor an unabashed celebration of their potential to transform the discipline, but a call to adopt new technologies and methods in a deliberate way that situates archaeological knowledge production in the realm of field practice.
Keywords: history of archaeology; slow movement; Taylorism; technology; digital archaeology.